Facemask and Respirator in Reducing the Spread of Respiratory Viruses; a Systematic Review - Shaterian, Negin; Abdi, Fatemeh; Atarodi Kashani, Zahra; Shaterian, Negar; Darvishmotevalli, Mohammad (Archives of Academic Emergency Medicine, 2021)
Introduction: Respiratory viruses spread fast, and some manners have been recommended for reducing the spread of these viruses, including the use of a facemask or respirator, maintaining hand hygiene, and perfoming social distancing. This systematic review aimed to assess the impact of facemasks and respirators on reducing the spread of respiratory viruses. Methods: We conducted a systematic review using MeSH terms, and reported findings according to PRISMA. PubMed, Embase, Cochrane Library, Scopus, ProQuest, Web of Science(WoS), and Google Scholar were searched for articles published between 2009 and 2020. Two independent reviewers determined whether the studies met inclusion criteria. The risk of bias of studies was assessed using Newcastle-Ottawa (NOS) and Consolidated Standards of Reporting Trials (CONSORT). Results: A total of 1505 articles were initially retrieved and 10 were finally included in our analysis (sample size: 3065). 96.8% of non-infected participants used facemask or respirator in contact with people infected with a respiratory virus, facemask and respirator have a significant effect on reducing the spread of respiratory viruses. Conclusion: Evidence support that using a facemask or respirator can reduce the spread of all types of respiratory viruses; therefore, this result can be generalized to the present pandemic of a respiratory virus (SARS-COV-2) and it is recommended to use a facemask or respirator for reducing the spread of this respiratory virus.